Answer:
Look at the attached graphic
We'll call b = 28 c = 32 and a=24
cos(A) = (b^2 + c^2 -a^2) / 2bc
cos(A) = (28^2 + 32^2 -24^2) / 2*28*32
cos(A) = (784 + 1024 - 576) / 1792
cos (A) = 1232 / 1792 = .6875
Angle A = 46.567 Degrees
cos(B) = (a^2 + c^2 -b^2) / (2ac)
cos(B) = (24^2 +32^2 -28^2) / (2*24*32)
cos(B) = (576 + 1024 -784) / 1536
cos(B) = 816 / 1536
cos (B) = .53125
Angle B = 57.91 Degrees
Since every triangle has a sum of 180 degrees then
Angle C = 180 -46.567 -57.91 = 75.523 degrees
Step-by-step explanation: